Reproducing a decision-making network in a virtual visual discrimination task - Trapani, Alessandra; Sheiban, Francesco Jamal; Bertone, Elisa; Chiosso, Serena; Colombo, Luca; D'Andrea, Matteo; De Santis, Francesco; Fati, Francesca; Fossati, Veronica; Gonzalez, Victor; Pedrocchi, Alessandra (Frontiers in Integrative Neuroscience, 2022)
We reproduced a decision-making network model using the neural simulator software neural simulation tool (NEST), and we embedded the spiking neural network in a virtual robotic agent performing a simulated behavioral task. The present work builds upon the concept of replicability in neuroscience, preserving most of the computational properties in the initial model although employing a different software tool. The proposed implementation successfully obtains equivalent results from the original study, reproducing the salient features of the neural processes underlying a binary decision. Furthermore, the resulting network is able to control a robot performing an in silico visual discrimination task, the implementation of which is openly available on the EBRAINS infrastructure through the neuro robotics platform (NRP).